1992
DOI: 10.1002/aic.690380708
|View full text |Cite
|
Sign up to set email alerts
|

Structure H clathrate hydrate equilibria of methane and adamantane

Abstract: The first phase equilibrium data are presented for Structure H hydrates. The data represent the initial formation of these hydrates from methane, with adamantane— a previously determined Structure H former. Temperature and pressure conditions are consistent with hydrocarbon production/transportation/processing facilities. Structure H hydrates are shown to contain molecules indigenous to petroleum. which may not be present in natural gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…These oil and condensate systems were traditionally regarded as non-hydrate forming systems. Secondly, phase equilibrium measurements of temperature and pressure conditions under which sH hydrates form a stable phase are consistent with those in hydrocarbon production, processing, and transportation facilities [4].…”
Section: Natural Gas Hydratessupporting
confidence: 64%
“…These oil and condensate systems were traditionally regarded as non-hydrate forming systems. Secondly, phase equilibrium measurements of temperature and pressure conditions under which sH hydrates form a stable phase are consistent with those in hydrocarbon production, processing, and transportation facilities [4].…”
Section: Natural Gas Hydratessupporting
confidence: 64%
“…In particular, the S H hydrate formation is becoming increasingly important in petrochemical processes due to the fact that some liquid components in petroleum are transformed into white, crystalline, solid S H hydrates by combining with moisture and light hydrocarbons existing in the plant and pipelines. Lederhos et al (4) reported the first S H hydrate phase equilibrium data of (methane + water + adamantane). Mehta and Sloan (5,6) also provided S H hydrate phase equilibrium data involving a variety of liquid hydrocarbons with methane as the guest components.…”
Section: Introductionmentioning
confidence: 98%
“…There are three types of cages in the s-H hydrate, pentagonal dodecahedron (5 12 , S-cage), dodecahedron (4 3 5 6 6 3 , S -cage) and icosahedron (5 12 6 8 , U-cage). The large guest molecules, such as adamantane (Lederhos et al, 1992), methylcyclohexane (Metha and Sloan, 1993;Mooijer-van den Heuvel et al, 2000;Sun et al, 2002) or other large guest species (Ripmeester and Ratcliffe, 1990;Metha and Sloan, 1994;Makino et al, 2004), can be entrapped in the U-cage while help gas occupies selectively both S-and S -cages. The structure of s-H hydrate becomes stable with the cooperative interaction between help gas and large guest species which is unable to generate s-H hydrate by itself.…”
Section: Introductionmentioning
confidence: 99%